Patient-led training on patient safety: A pilot study to test the feasibility and acceptability of an educational intervention. (25th March 2013) - Jha, V.; Winterbottom, A.; Symons, J.; Thompson, Z.; Quinton, N.; Corrado, O. J.; Melville, C.; Watt, I.; Torgerson, D.; Wright, J.
Abstract : Background : Training in patient safety is an important element of medical education. Most educational interventions on patient safety training adopt a 'health-professional lens' with limited consideration on the impact of safety lapses on the patient and their families and little or no involvement of patients in the design or delivery of the training. Aims : This paper describes a pilot study to test the feasibility and acceptability of implementing a patient-led educational intervention to facilitate safety training amongst newly qualified doctors. Method : Patients and/or carers who had experienced harm during their care shared narratives of their stories with trainees; this was followed by a focused discussion on patient safety issues exploring the causes and consequences of safety incidents and lessons to be learned from these. Results : The intervention, which will be further tested in an NIHR-funded randomised controlled trial (RCT), was successfully implemented into an existing training programme and found acceptance amongst the patients and trainees. Conclusion : The pilot study proved to be a useful step in refining the intervention for the RCT including identifying appropriate outcome measures and highlighting organisational issues.